2023
DOI: 10.1038/s41598-023-31166-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the ostiomeatal complex aeration using the CFD method

Abstract: We aimed to analyse ostiomeatal complex (OMC) aeration using the computational fluid dynamics (CFD) method of simulation based on human craniofacial computed tomography (CT) scans. The analysis was based on CT images of 2 patients: one with normal nose anatomy and one with nasal septal deviation (NSD). The Reynolds-Average Simulation approach and turbulence model based on linear eddy viscosity supplemented with the two-equation k-$$\omega$$ ω SST model were used for the CFD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It can be expected that the behavior of such flow systems are highly non-linear and three-dimensional. e.g., Tretiakow et al [ 160 ] found that the flow in the ostiomeatal complex (e.g., degree of turbulence) depended on the overall geometric features of the nasal cavity (e.g., nasal septum deviation).…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be expected that the behavior of such flow systems are highly non-linear and three-dimensional. e.g., Tretiakow et al [ 160 ] found that the flow in the ostiomeatal complex (e.g., degree of turbulence) depended on the overall geometric features of the nasal cavity (e.g., nasal septum deviation).…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
“…In silico studies are further grouped according to their modelling approach, Navier-Stokes-or Lattice-Boltzmann-based, as well as the turbulence modelling approach employed (laminar, RANS, LES, DNS). The present study [118,160,172,194,223] Spalart-Allmaras [204,226,246] Reynolds stress model [83] LES and RANS-LES hybrid models [83,148,204,206,217,237,247] [159, [248][249][250] The present study DNS [83] Lattice-Boltzmann-based methods (in silico) [42,125,195,[251][252][253] [127]…”
Section: Modelling Approaches In In Silico Studiesmentioning
confidence: 99%